FPGA for Robotic Applications: from Android/Humanoid Robots to Artificial Men - Tole Sutikno (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2011)
Researches on home robots have been increasing enormously. There has always existed a continuous research effort on problems of anthropomorphic robots which is now called humanoid robots. Currently, robotics has evolved to the point that different branches have reached a remarkable level of maturity, that neural network and fuzzy logic are the main artificial intelligence as intelligent control on the robotics. Despite all this progress, while aiming at accomplishing work-tasks originally charged only to humans, robotic science has perhaps quite naturally turned into the attempt to create artificial men. It is true that artificial men or android humanoid robots open certainly very broad prospects. This “robot” may be viewed as a personal helper, and it will be called a home-robot, or personal robot.